Cost-Benefit Analysis of Replacing Fish Meal with Black Soldier Fly (Hermetia illucens) Larvae Meal in Broiler Diets - Oladejo, O. A.; Fasoyiro, F. S.; Oguntunji, A. O.; Alabi, O. M.; Akintaro, O. G.; Kolawole, P. E. (Journal of Science, Technology and Innovation Research, 2026)
Rising inflation and overfishing have increased the cost and reduced the sustainability of fish meal, prompting the search for alternative protein sources in poultry production in Nigeria. This study evaluates the cost-benefit and performance outcomes of using black soldier fly larvae meal (BSFLM) as a substitute for fish meal in broiler diets. Fifty (50) broilers were assigned to five dietary treatments (T1, T2, T3, T4 and T5) with 0%, 25%, 50%, 75%, and 100% inclusion levels of BSFLM replacing fish meal over eight weeks. Data on daily feed intake, weekly body weight, and total feed cost were collected. Growth performance and economic indicators such as return on investment and cost-benefit ratio were analysed. Results showed that BSFLM inclusion significantly reduced feed costs without compromising broiler health or performance at 25–75% inclusion levels. Feed cost per 25 kg bag decreased from ₦33,317.50 ($20.95) in T5 to ₦18,525 ($11.65) in T1, demonstrating clear economic benefits. Return on Investment was highest in T4 (96.49%), followed by T5 (83.54%), both exceeding the control group (T1, 61.15%). While T1 had the highest feed intake and weight gain, T2 and T3 achieved comparable growth, indicating that partial fish meal replacement with black soldier fly larvae meal does not adversely affect the growth performance. These findings support black soldier fly larvae meal as a cost-effective and environmentally sustainable alternative to fish meal as an animal-based protein in broiler production, contributing to food security and sustainable agriculture. Keywords: Animal-based protein, Black soldier fly larvae meal, Cost-benefit-Ratio, Fish meal, Return on Investment